Dampak Kebijakan Alokasi Dana Desa (Add) Terhadap Pembangunan Desa Di Kabupaten Bulungan Tahun 2011 – 2014 - Slamet Hariyanto; Dyah Mutiarin (Universitas Muhammadiyah Yogyakarta, 2015)
Village Fund Allocation given to all villages in the district of Bulungan gives hope that the greater will be the realizationof equitable development, equitable and participatory. Village Fund Allocation policy implementation makes a verysignificant change, the village that was once get a very limited budget that is managed centrally by governmentagencies above the village are now getting a large enough budget and was given the authority to manage independently.The purpose of this study was to: (1) determine the impact of policies Village Allocation Fund in the SilvaRahayu Village, Tanjung Buka Village, Gunung Seriang Village, dan Bunyu Selatan Village, and (2) determine factorscausing variations in the impact of policies Village Allocation Fund in Silva Rahayu Village, Tanjung Buka Village,Gunung Seriang Village, dan Bunyu Selatan Village.The research is a qualitative research. This study was conducted inBulungan, precisely in the Silva Rahayu Village, Tanjung Buka Village, Gunung Seriang Village, dan Bunyu SelatanVillage. Data collected through interviews, observation, and documentation. The data analysis technique used is dataanalysis with qualitative methods to measure data collection, data reduction, data presentation, and conclusion.Theresults showed that the village has an impact Village Fund Allocation most suited to the purpose of the Village FundAllocation is expected Silva Rahayu village and the village of Tanjung Buka. Village at least in accordance with theoriginal purpose of the program is the Village Fund Allocation Bunyu Selatan Village. This is due to Silva Rahayu Villageand the Tanjung Buka Village has implemented the Village Fund Allocation program in accordance with the rules andregulations. The village is still having an inhibiting factor is the village of Tanjung Buka. The quantity and quality ofhuman resources in the village Tanjung Buka still fairly minimal and require further training. Silva Rahayu village,Gunung Seriang village, and the Bunyu Selatan Village not having problems associated with factors that can influencepolicy implementation Village Fund Allocation program. In all three villages of both quality and quantity of humanresources are sufficient to implement the Village Fund Allocation program. Human resources and apparatus also hasa mental attitude that is ready to implement the program properly.